2, 4, 5‐Trideoxyhexopyranosides derivatives of diphyllin: Synthesis and anticancer activity. (2nd June 2022) - Cai, Rui; Li, Yu; Zhu, Li; Wei, Caiyan; Bao, Xiaofeng; Zhao, Yu
Abstract: Diphyllin and its natural derivatives were identified as potent vacuolar H + ‐ATPase (V‐ATPase) inhibitors. In this study, twelve 2, 4, 5‐trideoxyhexopyranosides derivatives of diphyllin were synthesized. Most of these compounds showed potent abilities to inhibit the growth of HT‐29, MCF‐7, HepG2 cancer cells with IC50 values at submicromolar concentration. The compounds 5c3 and 5c4 showed the best inhibitory activity on breast cancer cell lines MCF‐7 with IC50 values of 0.09 and 0.10 μM. Compounds 5c3 and 5c4 showed similar V‐ATPase inhibitory potency to diphyllin. Molecular docking showed that a hydrogen bond was found between the hydroxyl of 5c3 and SerA534 in the pocket of the V‐ATPase receptor. Abstract : Twelve 2, 4, 5‐trideoxyhexopyranosides derivatives of diphyllin were synthesized by using divergent de novo glycosylation approach. They showed potent cytotoxicity and V‐ATPase inhibitory.